Plankton and environmental monitoring dataset from the Iroise Marine Natural Park (NE Atlantic, 2010-2023) ... - Drago, Laetitia; Cailliau, Caroline; Pouline, Patrick; Beker, Beatriz; Jalabert, Laëtitia; Romagnan, Jean-Baptiste; Ayata, Sakina-Dorothée (SEANOE, 2025)
This dataset presents a long-term monitoring record of phytoplankton (2010-2022) and zooplankton (2010-2023) taxonomic groups, alongside associated environmental parameters (surface and bottom temperature and salinity measurements) from the Iroise Marine Natural Park, France's first Marine Protected Area. The dataset integrates traditional microscopy-based phytoplankton counts with zooplankton imaging data obtained using the ZooScan (Gorsky et al., 2010), as well as zooplankton biovolume and concentration data. Sampling was conducted seasonally along two main coastal-offshore transects (B and D) and at three coastal stations (Molène, Sein, and Douarnenez), capturing the spatial and temporal dynamics of plankton communities in this unique ecosystem located at the intersection of the English Channel and the Atlantic Ocean. The region is characterized by the seasonal Ushant thermal front, which creates diverse habitats supporting rich plankton communities. Phytoplankton identification was performed consistently ...